PENGARUH GOOD CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA - Ita Trisnawati; Frengky; Dicky Supriatna (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research aims to obtain empirical evidence on whether the components of good corporate governance and company characteristics influence earnings management. This research has eleven independent variables, namely audit quality, board of commissioners, managerial ownership, auditor independence, institutional ownership, audit committee, profitability, firm size, free cash flow, financial leverage, and sales growth. This research used a sample of 210 data from 70 manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 to 2021. This study used a purposive sampling method for sample selection and used multiple regression for data analysis. The results of this research indicate that audit quality, profitability, and free cash flow affect earnings management. However, other independent variables such as the board of commissioners, auditor independence, audit committee, institutional ownership, financial leverage, firm size, sales growth, and managerial ownership do not affect earnings management.